Pengaruh Metode Pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite, Review) Terhadap Hasil Belajar TIK Siswa Kelas VIII - Ida Ayu Widiyanthi; Nyoman Sugihartini; Dessy Seri Wahyuni; Made Windu Antara Kesiman (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
The aims of this study are (1) to know the effect of the implementation of PQ4R learning method toward students’ learning result in the topic of Microsoft Word application program, (2) to know students’ learning activities toward the implementation of PQ4R learning method, (3) to know students’ response toward the implementation of PQ4R learning method.The type of this research was quasi experiment with Posttest-Only Control Group Design. The population of this research was students of eigth grade in SMP Negeri 1 Sukasada academic year of 2013/2014. The samples of this research were VIII G class as the experiment group and VIII E class as the control group. The data in this research were gathered by using multiple choice tests to measure the cognitive competence of students. Data was analyzed by studying the results of test preconditions including normality test, homogeneity test, and t-test. Students’ learning activities is using the observation method, for the response is using the questionnaire method.Based on the analysis of the data, obtained that tests of normality and homogeneity of the two groups were normally distributed and homogeneous. There was a significant effect of the implementation of PQ4R learning method toward students’ learning result of the ICT subject in the eigth grade students in SMP Negeri 1 Sukasada academic year of 2013/2014. Students’ learning activities in the experiment group were quite active in the learning process, and the students also gave positive responds toward the use of PQ4R learning method.